The atmospheric entry of fine‐grained micrometeorites: The role of volatile gases in heating and fragmentation. (30th November 2018) - Suttle, M. D.; Genge, M. J.; Folco, L.; Van Ginneken, M.; Lin, Q.; Russell, S. S.; Najorka, J.
Abstract: The early stages of atmospheric entry are investigated in four large (250–950 μm) unmelted micrometeorites (three fine‐grained and one composite), derived from the Transantarctic Mountain micrometeorite collection. These particles have abundant, interconnected, secondary pore spaces which form branching channels and show evidence of enhanced heating along their channel walls. Additionally, a micrometeorite with a double‐walled igneous rim is described, suggesting that some particles undergo volume expansion during entry. This study provides new textural data which links together entry heating processes known to operate inside micrometeoroids, thereby generating a more comprehensive model of their petrographic evolution. Initially, flash heated micrometeorites develop a melt layer on their exterior; this igneous rim migrates inwards. Meanwhile, the particle core is heated by the decomposition of low‐temperature phases and by volatile gas release. Where the igneous rim acts as a seal, gas pressures rise, resulting in the formation of interconnected voids and higher particle porosities. Eventually, the igneous rim is breached and gas exchange with the atmosphere occurs. This mechanism replaces inefficient conductive rim‐to‐core thermal gradients with more efficient particle‐wide heating, driven by convective gas flow. Interconnected voids also increase the likelihood of particle fragmentation during entry and, may therefore explain the rarity of large fine‐grained micrometeorites among collections.